La Ciguatera - Jorge R. Rey (EDIS)
ENY-741S, a 5-page illustrated fact sheet by Jorge R. Rey, is the Spanish language version of ENY-741, Ciguatera. It describes this form of food poisoning caused by ingestion of saltwater fish and invertebrates that have accumulated in their tissues a certain amount of the toxins produced by dinoflagellates. Includes references. Published by the UF Department of Entomology and Nematology, November 2007.